Emotional intelligence and stress coping strategies in health care workers.: Inteligencia emocional y estrategias de afrontamiento al estrés en personal de salud. - Traverso Zumaeta, Roxana (2023)
Objective: To determine the relationship between emotional intelligence and stress coping strategies in health care workers of a Third Level of Care Hospital during 2021. Methods: An analytical cross-sectional study was carried out. Two surveys were used: the COPE test which measures how to cope with stress and the Bar-On Emotional Coefficient Inventory which measures the level of emotional intelligence. The main variable was coping with stress. The independent variable was emotional intelligence. Results: A total of 290 health care workers were worked. Emotional intelligence was significantly positively correlated (Pearson = 0.6003) with stress coping. The stress coping strategies with the highest mean were planning, positive reinterpretation and growth, and religious coping. These strategies had a positive correlation with emotional intelligence, these correlations were 0.5271, 0.5200 and 0.2051 respectively. For the multiple regression analysis, it was observed that the average BARON test score increased by 0.261 points for each point increase in the COPE TEST (coefficient = 0.261; 95%CI: 0.215 - 0.307); adjusted for all covariates of interest. Conclusion: There is a relationship between emotional intelligence and stress coping. A relationship was also found with stress coping strategies.